2014
DOI: 10.3126/jkmc.v2i4.11799
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Management of Uterovesical Fistula Following Primary Caesarean Section

Abstract: Uterovesical fistula is an abnormal communication between uterine cavity and the bladder. It is a rare type of fistula accounting for four percent of all cases of urogenital fistula. However the incidence of uterovesical fistula has been rising due to increasing incidence of lower segment caesarean section. Uterovesical fistula is seen more after repeated caesarean section rather than primary section. This is a case report of a primipara with uterovesical fistula following primary emergency Caesarean section o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…3,19 Urinary infection is treated with a conservative approach and the patient is followed up for three weeks via catheterizing the bladder. Surgical approach is performed for all wide fistulas and small fistulas that do not have spontaneous recovery after a three-month conservative followup.…”
Section: Discussionmentioning
confidence: 99%
“…3,19 Urinary infection is treated with a conservative approach and the patient is followed up for three weeks via catheterizing the bladder. Surgical approach is performed for all wide fistulas and small fistulas that do not have spontaneous recovery after a three-month conservative followup.…”
Section: Discussionmentioning
confidence: 99%
“…Small fistula can be treated conservatively if detected early with a reported success rate of 5%. [ 8 ] For large and/or nonhealing fistula, surgical approach is preferred. Options include open and minimally invasive (laparoscopic/robotic) procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical management is definite for Youssef's syndrome; however, conservative measures such as prolonged catheterization to aid in fistula healing, and medical management like the use of oral contraceptives, progestational agents, local estrogen and gonadotropin-releasing hormone analogue for the induction of amenorrhea, have been reported in the literature with successful outcomes. [16][17][18][19] Small fistulas (<1 cm) may resolve if continuous drainage of the bladder is maintained. In 1985, Zimmern concluded that fistulas have a high spontaneous cure rate with a 3week trial of Foley drainage.…”
Section: Discussionmentioning
confidence: 99%